UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMA DALAM PEMBELAJARAN BERBANTU SOFTWARE MICROSOFT MATHEMATICS VERSI 4.0 - Nining Cartini; Rifqi Hidayat; Desy Lusiyana (Integral : Pendidikan Matematika, 2018)
Research is motivated by the low ability of students' mathematical creative thinking in learning. The purpose of this study is to determine the increase in student learning activities in the learning process of mathematics and improvement of mathematical creative thinking of high school students in the process of learning mathematics using the learning media Microsoft Mathematics Version 4.0. This classroom action research uses inquiry method. The sample in this research is class X MIPA 1. The sample is determined pursuant to Purposive sampling. Instruments used in research in the form of students' mathematical creative thinking ability test. Based on the results of pretest students class X MIPA 1 students who achieve 0% KKM completeness. Followed by postes result in cycle 1 mastery 35% KKM and postes result in cycle II got KKM completeness 79,8%. 44.8% increase in KKM completeness from cycle I to cycle II. The answer of the student questionnaire sheet increased 5% from cycle I to cycle II. Based on the fact that learning assisted Software Microsoft Mathematics Version 4.0 improve student learning activities and improve the ability to think creatively mathematically high school students 3 Kuningan. Keywords: Creative thinking mathematically, Microsoft Mathematics Software Version 4.0